Keeping it Clean: Controlling Mildew - Mary N. Harrison (EDIS)
Mildew is a mold that can grow and cause damage to your health and home. You should be concerned about mildew because it makes respiratory problems, like asthma, worse. This document is FCS5232-11, one of a series on Home Cleaning and Repairing of the Department of Family, Youth and Community Sciences, UF/IFAS Extension. Original publication date June 2002. Revised November 2005.